2005
DOI: 10.1002/app.21465
|View full text |Cite
|
Sign up to set email alerts
|

Properties and thermal degradation study of blend films with poly(4‐vinylpyridine) and lignin

Abstract: A series of blend films with different ratio of poly(4-vinylpyridine) (PVP) to lignin were subjected to dynamic DSC and TGA measurement under nitrogen atmosphere at various heating rates. DSC curves showed that the glass transition temperatures of these blends decreased with the increase of lignin content. TGA studies indicated that the lignin content produced obvious effect on the thermal stability of these blends. The kinetic model function of the thermal decomposition of these blends obeyed the Avrami-. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Miscibility was claimed for other polymers as well. Liu et al [120,121] found that poly(4-vinylpyridine) is miscible with lignin and a similar conclusion was drawn about poly(vinylpyrrolidone)/lignin blends by Silva et al [122], as well as about polypolyanlinine/lignin blends by Rodrigues et al [114]. This latter group studied its blends with FTIR spectroscopy and cyclic voltammetry and drew this conclusion from the results.…”
Section: Other Polymers H-bondsmentioning
confidence: 66%
See 1 more Smart Citation
“…Miscibility was claimed for other polymers as well. Liu et al [120,121] found that poly(4-vinylpyridine) is miscible with lignin and a similar conclusion was drawn about poly(vinylpyrrolidone)/lignin blends by Silva et al [122], as well as about polypolyanlinine/lignin blends by Rodrigues et al [114]. This latter group studied its blends with FTIR spectroscopy and cyclic voltammetry and drew this conclusion from the results.…”
Section: Other Polymers H-bondsmentioning
confidence: 66%
“…On the other hand, plastics containing aromatic rings can form also stronger,  stacking interactions, thus better compatibility, partial miscibility and better properties can be expected upon the blending of the two components. Numerous papers have been published on such blends and the controversy characterizing the study of polyolefin/lignin blends can be observed also for Miscibility was claimed also for a number of other polymers containing aromatic rings, like poly(4-vinyl pyridine) [112,113] and polyaniline [114], but most of the polymers including PET form not only  electron interactions, but also H-bonds with lignin. Considering all the information offered in the papers published on aromatic polymer/lignin blends, we can conclude that interactions are generally stronger in these blends than in polyolefin/lignin combinations [115].…”
Section: Polymers With Aromatic Ringsmentioning
confidence: 99%
“…Composites and blends of lignin with cellulose [39], cellulose acetate [40], xanthan gum [41], PEG [42], PVA [43], PLA [44], PVP [45,46] are known from the literature. Even though there may be only weak interaction between lignin and principal constituent, addition of lignin may offer advantages such as more control over water uptake [41] and improved mechanical properties [31,45].…”
Section: Q2mentioning
confidence: 99%
“…Miscibility was claimed for other polymers as well. Liu et al [38,39] found that poly(vinyl pyrrolidone) is miscible with lignin. A similar conclusion was drawn about polyaniline/lignin blends by Rodrigues at al.…”
Section: Introductionmentioning
confidence: 99%